Clima organizacional y satisfacción laboral en los colaboradores de una cadena de supermercados en la ciudad de Cali, 2021 (2021)
This research work seeks to establish the relationship between the organizational climate and the job satisfaction of the collaborators of a supermarket chain in the area located in the city of Santiago de Cali. In this sense, a quantitative analysis was carried out to have an approach to reality in a given context, in order to identify the organizational climate with respect to job satisfaction. Among the conclusions, it is indicated that there is a high correspondence between job satisfaction and organizational climate, employees have an average job satisfaction of 44% as well as a regular perception regarding the organizational climate of 36%. It is possible to affirm that there is a high correlation between the two categories analyzed in the present research study